Factors Affecting the Selection of Health Insurance: An Empirical Study - Bawa, Sumninder Kaur; Verma, Ruchita (Prabandhan: Indian Journal of Management, 2012)
There is a dire need to study the state of health insurance as well as factors affecting the selection of health insurance by an individual. The reason is attributable to the fact that, firstly; this is one of the growing businesses and secondly; it is the need of the hour. Human beings can manage to live without good educationâ€¦without a splendid carâ€¦without an opulent houseâ€¦, but no one can manage to live without good and excellent health, that too when he/she is living below the poverty line. One of the solutions to this is to take a health insurance scheme which is a widely recognized mechanism to finance health care of an individual, because he/she has to just make gradual contribution towards the premium of the insurance and he/she can get rid of health worries. So, the present study is an effort in the field of health insurance - to investigate and to examine the various factors affecting the selection of health insurance by an individual. For this, a sample of 180 respondents has been considered from the Amritsar district of Punjab. Thereafter, the use of Factor Analysis has been made, which shows that there are seven key factors (by clubbing the related variables), which widely affect and govern the selection of health insurance by an individual. These key factors are namely: Ease with which the services can be obtained; Minimum Consideration; Availability of Funds (whether in hand or from outside); Intermediaries’ Outreach and Capabilities; Multiplicity of Benefits with Extensive Promotional Activities; Goodwill and Linkage of the Company with Third Party Administrators (TPAs); and Operating with Customers’ Oriented Modern Technology.